2006
DOI: 10.2136/vzj2005.0133br
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Methods for Flow in Porous Media: Coping with Uncertainties

Abstract: DONGXIAO ZHANG. Academic Press, San Diego, CA. 2002. Hardcover, 350 pp. $89.95. ISBN: 0-12-779621-5. Hydrogeological variables of a groundwater system, for example, the hydraulic head and contaminant concentration, vary with space and time. The variability is due to spatial heterogeneities of geological materials and temporal variations of the internal and external input to and output from the groundwater system, such as groundwater recharge, evapotranspiration, and base flow to streams. These spatial hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
224
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(232 citation statements)
references
References 3 publications
1
224
0
7
Order By: Relevance
“…A variety of methods for propagating parameter uncertainty are available, including Monte Carlo simulation, the first-order, second-moment method (Kunstmann et al 2002;Vecchia and Cooley 1987), the stochastic response surface method (Isukapalli et al 1998), and stochastic moment methods (Dagan and Neuman 1997;Zhang 2001). Monte Carlo simulation is the most generally applicable method.…”
Section: Analysis Of Parameter Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of methods for propagating parameter uncertainty are available, including Monte Carlo simulation, the first-order, second-moment method (Kunstmann et al 2002;Vecchia and Cooley 1987), the stochastic response surface method (Isukapalli et al 1998), and stochastic moment methods (Dagan and Neuman 1997;Zhang 2001). Monte Carlo simulation is the most generally applicable method.…”
Section: Analysis Of Parameter Uncertaintymentioning
confidence: 99%
“…The stochastic moment methods are appealing because of their potential computational advantage over Monte Carlo simulation. Recent progress in handling conditions that introduce nonstationarities (Zhang 2001) have made these methods more generally applicable.…”
Section: Analysis Of Parameter Uncertaintymentioning
confidence: 99%
“…In this framework, the main parameters controlling the degree of heterogeneity were the variance of the logarithm of the hydraulic conductivity and its correlation length. An extremely broad range of important results have been obtained using this model in the stochastic hydrogeology literature [3][4][5][6]. But several authors raised the point that the multi-Gaussian model was too restrictive and could not describe the full range of connectivity patterns that one finds in nature [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To model such a variability it is customary to adopt the stochastic approach (an exhaustive exposition can be found in the monographs of Zhang 2002;Rubin 2003) which regards the hydraulic conductivity as a stationary RSF. As a consequence, the flow variables will result RSFs as well, and one of the main issue consists into: (1) determining their mean values, and (2) quantifying the associated uncertainty (see e.g., Beran 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The configuration mostly studied in the past is that of uniform flows in the average (a situation which is ascribed to natural gradient conditions). Mean uniform flows have been investigated experimentally by controlled field tests (e.g., Sudicky 1986; LeBlanc et al 1991), and theoretically by means of numerical codes (a wide review can be found in Zhang 2002;Rubin 2003), as well as of analytical tools (Dagan 1989). There are however many hydrological applications (such as protection zones of wells, pump and treat remediation procedures, pumping tests analysis) of non uniform mean flows.…”
Section: Introductionmentioning
confidence: 99%